Repairing the world: faith against online hate - Greenberg, Yudit (2022)
In a world of instant communication and social media, the ease with which hate, and bias spread compels us to rethink our approach in education and community learning. It is important for the state, educators, and religious actors to actively involve themselves in anticipating the different means in which this hatred is expressed, educating people, and developing preventive measures to protect faith communities in every country.